2013
DOI: 10.5152/balkanmedj.2012.098
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Effects ofIvermectin and Sulphadiazine on Toxoplasma gondii

Abstract: Objective: Ivermectin and sulphadiazine were tested individually to determine their in vitro effects on Toxoplasma gondii grown in human epidermoid larynx carcinoma (Hep-2) cell culture.Study Design: In-vitro study.Material and Methods: Toxoplasma growth was quantities by an enzyme immunoassay performed directly on the fixed cultures, using a rabbit anti-T. gondii immunoglobulin G as the first antibody and a phosphatase-labeled anti-rabbit immunoglobulin G as the second antibody. For each drug, regression mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Since the approval of the use of ivermectin in humans, the drug has been tested against a variety of human parasitic diseases, as reviewed previously (31,32), but it was suggested that it was inactive against bacteria, fungi, flatworms, and protozoans (33). However, recent publications described in vitro activity of ivermectin against flavivirus (34), bacterial species (35)(36)(37), Toxoplasma gondii (38), and Trypanosoma brucei (39).…”
Section: Discussionmentioning
confidence: 99%
“…Since the approval of the use of ivermectin in humans, the drug has been tested against a variety of human parasitic diseases, as reviewed previously (31,32), but it was suggested that it was inactive against bacteria, fungi, flatworms, and protozoans (33). However, recent publications described in vitro activity of ivermectin against flavivirus (34), bacterial species (35)(36)(37), Toxoplasma gondii (38), and Trypanosoma brucei (39).…”
Section: Discussionmentioning
confidence: 99%
“…Other compounds such as amino-terpenyl naphthoquinones, b-carboline alkaloids, analogues dextran sulfate, bisphosphonates, ferrocenyl aminohydroxynaphthoquinones, and ivermectin displayed anti-parasitic properties toward T. gondii, however the mechanism of this activity has not been explained [60][61][62][63][64][65].…”
Section: Other Synthetic Compoundsmentioning
confidence: 94%